Grandparents’ Lived Experience in Caring for Grandchildren: A Qualitative Study - Mouladoost, Akram; Namdarpour, Fahimeh; Tabrizi, Mehdi (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The purpose of the present study was to explore the lived experience of grandparents in caring for grandchildren. Methods and Materials: The present research was qualitative in nature and based on an interpretative phenomenological approach. From among older adults who had experience in caring for grandchildren, the researcher purposefully selected 20 elderly participants (10 grandfathers and 10 grandmothers) and conducted interviews with them. All interviews were recorded, transcribed, and finally analyzed using the interpretative phenomenological analysis method of Diekelmann et al. (1989). Findings: Analysis of the participants’ statements led to the identification of 107 initial concepts, 16 sub-themes, and four main themes (aging-related problems, challenges of older adults in caring for grandchildren, positive consequences of caring for grandchildren in older adults, and consequences of care in grandchildren). Conclusion: The results clearly illuminated the problems and challenges of caring for grandchildren, as well as the positive effects of this process on both grandparents and grandchildren. Experts can utilize these findings to design preventive, educational, and even therapeutic programs aimed at realizing constructive grandchild care and reducing its potential negative outcomes.